2018
DOI: 10.3389/fimmu.2018.00947
|View full text |Cite
|
Sign up to set email alerts
|

NY-ESO-1 Based Immunotherapy of Cancer: Current Perspectives

Abstract: NY-ESO-1 or New York esophageal squamous cell carcinoma 1 is a well-known cancer-testis antigen (CTAs) with re-expression in numerous cancer types. Its ability to elicit spontaneous humoral and cellular immune responses, together with its restricted expression pattern, have rendered it a good candidate target for cancer immunotherapy. In this review, we provide background information on NY-ESO-1 expression and function in normal and cancerous tissues. Furthermore, NY-ESO-1-specific immune responses have been o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
233
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(235 citation statements)
references
References 153 publications
0
233
1
1
Order By: Relevance
“…This is supported by prior studies which suggest that cancer-specific overexpression of non-mutant antigens may comprise the majority of tumor-associated antigens [43][44][45][46] . NY-ESO-1, or cancer testis antigen 1B (CTGAG1B), has been well-characterized as an antigen that elicits humoral immune responses in various cancers including melanoma and breast, lung, bladder, ovarian, and prostate cancers [47][48][49] . Additionally, given its cancer-specific expression pattern outside of the testes [49][50][51][52] , NY-ESO-1 has shown great promise as a potential target for T-cell immunotherapies in various cancers 47 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is supported by prior studies which suggest that cancer-specific overexpression of non-mutant antigens may comprise the majority of tumor-associated antigens [43][44][45][46] . NY-ESO-1, or cancer testis antigen 1B (CTGAG1B), has been well-characterized as an antigen that elicits humoral immune responses in various cancers including melanoma and breast, lung, bladder, ovarian, and prostate cancers [47][48][49] . Additionally, given its cancer-specific expression pattern outside of the testes [49][50][51][52] , NY-ESO-1 has shown great promise as a potential target for T-cell immunotherapies in various cancers 47 .…”
Section: Discussionmentioning
confidence: 99%
“…NY-ESO-1, or cancer testis antigen 1B (CTGAG1B), has been well-characterized as an antigen that elicits humoral immune responses in various cancers including melanoma and breast, lung, bladder, ovarian, and prostate cancers [47][48][49] . Additionally, given its cancer-specific expression pattern outside of the testes [49][50][51][52] , NY-ESO-1 has shown great promise as a potential target for T-cell immunotherapies in various cancers 47 . In our unbiased approach to identifying immunogenic antigens, we found that NY-ESO-1 was the top candidate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that tumors possessing these antigens are more likely to induce tolerance and are less responsive to ICB (further explained below) (22,23). In addition, they induce more autoreactivity when targeted by adoptive cell therapy (ACT) (31)(32)(33)(34)(35)(36).…”
Section: Tumor Immunosurveillance and Tumor Antigensmentioning
confidence: 99%
“…Peripheral T cells were then engineered to express TCRs against specific tumor neo-antigens in highly mutated tumors such as melanoma and lung cancer (83)(84)(85)(86)(87)(88)(89)(90). Adoptively transferred genetically engineered lymphocytes directed against specific NY-ESO-1 epitopes, a well-known cancer-testis antigen, have shown promising clinical responses across a number of tumors (35). This and other potential TCR targets are currently being investigated, as part of engineered T cell treatments, in clinical trials for lung cancers including NSCLC (NCT03778814) (35).…”
Section: Adoptively Transferred Tumor Reactive T Cellsmentioning
confidence: 99%